2021
DOI: 10.1101/2021.05.31.446450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TORC1 and PKA activity towards ribosome biogenesis oscillates in synchrony with the budding yeast cell cycle

Abstract: Recent studies have revealed that the growth rate of budding yeast and mammalian cells varies during the cell cycle. By linking a multitude of signals to cell growth, the highly conserved Target of Rapamycin Complex 1 (TORC1) and Protein Kinase A (PKA) pathways are prime candidates for mediating the dynamic coupling between growth and division. However, measurements of TORC1 and PKA activity during the cell cycle are still lacking. Following the localization dynamics of two TORC1 and PKA targets via time-lapse… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 100 publications
(147 reference statements)
1
2
0
Order By: Relevance
“…A recent study employing an inertial picobalance and microscopy showed that the growth rate of yeast cells in S/G2/M has a non-monotonic pattern similar to the protein synthesis rate dynamics observed in this work 60 . Furthermore, TORC1 and PKA activity toward ribosome biogenesis was recently reported to have two waves per cell cycle 21 and we found (with two completely orthogonal single-cell methods) that protein synthesis has two activity peaks during the cell cycle. This suggests that the existing notion of a constant/exponential protein biosynthesis rate during the cell cycle needs to be revised.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…A recent study employing an inertial picobalance and microscopy showed that the growth rate of yeast cells in S/G2/M has a non-monotonic pattern similar to the protein synthesis rate dynamics observed in this work 60 . Furthermore, TORC1 and PKA activity toward ribosome biogenesis was recently reported to have two waves per cell cycle 21 and we found (with two completely orthogonal single-cell methods) that protein synthesis has two activity peaks during the cell cycle. This suggests that the existing notion of a constant/exponential protein biosynthesis rate during the cell cycle needs to be revised.…”
Section: Discussionsupporting
confidence: 55%
“…The agreement between two independent methods to determine protein production dynamics, first, validated our new stopand-respond method to infer metabolic activity during the cell cycle. Second, both methods revealed that protein biosynthesis has two activity waves during the cell cycle, one peaking around START and the other in the middle of S/G2/M, opposite to the current notion of protein biosynthesis dynamics [3][4][5][6][7] , but in line with the recent finding of cell-cycle-dependent activity of TORC1 and PKA toward ribosome biogenesis 21 . The protein biosynthesis activity has a minimum around budding as well as 10-20 min before mitotic exit (Fig.…”
mentioning
confidence: 57%
“…After verification of the genome editing event(s) by PCR and/or Sanger sequencing, the Cas9+sgRNA(s) multi-gene plasmid is removed from yeast cells. In our lab, we have successfully used this procedure to generate several mutations at the SCH9 locus, encompassing full gene knockout, deletion of specific gene regions, and domain replacement ( Novarina et al., 2021 ), as well as to perform gene knockouts and to introduce point mutations in several yeast genes ( Guerra et al., 2021 ).
Figure 1 Schematic of the sgRNA(s) and Cas9 cloning through Golden Gate assembly The sgRNA and the Cas9 gene are cloned in a yeast expression vector through three consecutive Golden Gate assembly reactions.
…”
Section: Before You Beginmentioning
confidence: 99%